2015
DOI: 10.1161/circulationaha.114.012669
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Adamts7 , a Novel Coronary Artery Disease Locus in Humans, Reduces Atherosclerosis in Mice

Abstract: Background Genome-wide association studies (GWAS) have established ADAMTS7 as a locus for coronary artery disease (CAD) in humans. Yet, these studies fail to provide directionality for the association between ADAMTS7 and CAD. Previous reports have implicated ADAMTS7 in the regulation of vascular smooth muscle cell (VSMC) migration, but a role and direction of impact for this gene in atherogenesis has not been shown in relevant model systems. Methods and Results We bred an Adamts7 whole body knockout (KO) mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
137
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(149 citation statements)
references
References 30 publications
10
137
1
1
Order By: Relevance
“…In the meantime, two studies investigating the role of ADAMTS7 in mouse models revealed evidence that mice lacking Adamts‐7 ( Adamts7 −/− ) display reduced atherosclerotic plaque formation compared to WT littermates when they are on a proatherogenic background and fed a western diet. This effect was most prominent in Adamts7 −/− Ldlr −/− mice with a strong reduction in plaque formation in the aortic root as well as in the en face whole aorta analysis (Bauer et al , 2015). The mechanism underlying this phenotype is still unclear.…”
Section: Vascular Remodellingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, two studies investigating the role of ADAMTS7 in mouse models revealed evidence that mice lacking Adamts‐7 ( Adamts7 −/− ) display reduced atherosclerotic plaque formation compared to WT littermates when they are on a proatherogenic background and fed a western diet. This effect was most prominent in Adamts7 −/− Ldlr −/− mice with a strong reduction in plaque formation in the aortic root as well as in the en face whole aorta analysis (Bauer et al , 2015). The mechanism underlying this phenotype is still unclear.…”
Section: Vascular Remodellingmentioning
confidence: 99%
“…The second study focused on vascular remodelling. Adamts7 −/− mice displayed strongly reduced neointima formation after wire‐mediated vascular injury (Bauer et al , 2015; Kessler et al , 2015), a phenotype that is supposed to be mainly mediated by beneficial effects in endothelial cells (Kessler et al , 2015). Endothelial cells of Adamts7 −/− mice showed increased proliferation and migration in vitro .…”
Section: Vascular Remodellingmentioning
confidence: 99%
“…These new resources and techniques have already provided important mechanistic insights for several novel susceptibility loci for CAD, including those regions harboring the genes CDKN2B, SORT1, TCF21, ADAMTS7, SMAD3, and other loci (165)(166)(167)(168)(169)(170)(171)(172). Although this understanding has not yet been translated to therapeutic agents targeting these loci, the rapid path of translation for other susceptibility loci, such as PCSCK9, provides some reassurance that such developments are forthcoming and are likely to provide us with groundbreaking opportunities to further reduce, and possibility eliminate, the threat of CAD in the 21 st century.…”
Section: Future Directionsmentioning
confidence: 99%
“…Studies are also needed to investigate whether atherosclerosis-associated ADAMTS7 genetic variants are associated with restenosis or arterial calcification, as recently suggested. 6 Overall, the studies presented by Bauer at al 5 provide the first firm evidence that mouse Adamts7 plays a proatherogenic role, likely through the promotion of VSMC migration. The long-term success of percutaneous coronary intervention is limited by restenosis, a pathological process characterized by excessive neointimal thickening caused by the inflammatory response associated with mechanical injury to the vessel wall.…”
Section: Articles See P 1191 and P 1202mentioning
confidence: 95%
“…In this issue of Circulation, Bauer and colleagues 5 directly address this hypothesis by generating whole-body knockout mice for Adamts7 for the investigation of atherosclerosis development. The authors crossed Adamts7-null mice with the atherosusceptible apoE knockout and Ldlr knockout mouse models and found that deletion of Adamts7 significantly reduced atherosclerotic lesion formation in the aortas and aortic roots of both hyperlipidemic strains.…”
Section: Articles See P 1191 and P 1202mentioning
confidence: 99%